Perceived organizational politics: Implications for nurses’ stress and job satisfaction - Yennuten Paarima; Asongo Akwobi Kisinna; Adelaide Maria Ansah Ofei (International Journal of Africa Nursing Sciences, 2024)
Background: Perceived organizational politics is a common phenomenon in almost every organization and is associated with undesirable employee outcomes. Despite numerous studies on this important topic, studies describing the influence of perceived organizational politics on nurses' outcomes (job satisfaction and stress) remain underinvestigated. This study examined the impact of perceived organizational politics on job satisfaction and job stress among nurses. Methods: A quantitative cross-sectional design was used in this study. Two hundred and thirteen (213) nurses participated. Three standardized instruments were utilized: Perception of Organizational Politics, Job Satisfaction Scale, and Job Stress Scale. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analyses. Findings: Nurses perceived a high level of organizational politics. We identified a significant correlation between perceived organizational politics, job stress, and job satisfaction in nursing. The results showed nurses' perception of organizational politics had a positive relationship with job stress and a negative relationship with job satisfaction. Managerial implication: Hospital management should reconsider the organizational, group, and individual situations that create perceived organizational politics to prevent any unnecessary political behaviors in the hospital. Also, strategies to enhance nursing management and healthcare provision should be directed at reducing the use of politics to promote self-interest. Originality/value: Our study provides a novel insight into the unexplored nature and impact of perceived organizational politics on nurses' job satisfaction and stress in Ghana. It is the first research to investigate organizational politics using nursing population in the Ghanaian context and makes significant contributions to theory and practice.